Finnish and Swedish Business Cycles in a Global Context - Michael Bergman (Lund University, School of Economics and Management, Department of Economics, 2001)
This paper examines the characteristics of business cycles in and across Sweden and Finland during the postwar period. We find that output fluctuations in Sweden and Finland are highly correlated to two measures of the international business cycle, a European and a non–European common business cycle component. The Swedish but not the Finnish business cycle becomes more synchronized to the European business cycle over time whereas the Finnish but not the Swedish business cycle becomes more synchronized to the non–European business cycle. We also find that country–specific business cycles in Finland and Sweden are highly synchronized only during the 1990's.
Keywords: E32; F41; 330; Finnish and Swedish business cycles; World business cycle; European business cycle; symmetry and comovement of cycles